2021
DOI: 10.3390/cancers13081859
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High Dose Rate Transmission Beam Proton Therapy for Conventionally Fractionated Head and Neck Cancer: Treatment Planning and Dose Rate Distributions

Abstract: Transmission beam (TB) proton therapy (PT) uses single, high energy beams with Bragg-peak behind the target, sharp penumbras and simplified planning/delivery. TB facilitates ultra-high dose-rates (UHDRs, e.g., ≥40 Gy/s), which is a requirement for the FLASH-effect. We investigated (1) plan quality for conventionally-fractionated head-and-neck cancer treatment using spot-scanning proton TBs, intensity-modulated PT (IMPT) and photon volumetric-modulated arc therapy (VMAT); (2) UHDR-metrics. VMAT, 3-field IMPT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…( 8) only gives a conservative crude estimate of a "global" dose rate for the 4-spot pattern due to the nonuniform spatial distribution of the dose rate within the field (the areas corresponding to the center of each spot have higher "local" or voxel-specific dose rate compared to the central region of the field where the spots overlap). Definition of the dose rate in the context of FLASH for the scanning beams is not straightforward 33,34 and is beyond the scope of this work.…”
Section: Optimization Of the Range Modulatormentioning
confidence: 99%
“…( 8) only gives a conservative crude estimate of a "global" dose rate for the 4-spot pattern due to the nonuniform spatial distribution of the dose rate within the field (the areas corresponding to the center of each spot have higher "local" or voxel-specific dose rate compared to the central region of the field where the spots overlap). Definition of the dose rate in the context of FLASH for the scanning beams is not straightforward 33,34 and is beyond the scope of this work.…”
Section: Optimization Of the Range Modulatormentioning
confidence: 99%
“…This spread of dose across the beam spot is a noted difficulty with delivering FLASH using PBS however the necessary instantaneous, mean or threshold dose over a region of interest, has not yet been quantitatively defined ( 177 ). The impact of deadtimes is also unclear, as PBS parameters (components in Section 2.2) determine the dose output and timing ( 178 ). Hybrid delivery schemes and 3D modulation devices have been suggested for reaching FLASH dose rates across the entire volume however higher beam intensities are needed to compensate particle losses.…”
Section: Emerging Applicationsmentioning
confidence: 99%
“…Furthermore, as ensuring precise beam delivery and positioning is difficult, transmission or ‘ shoot-through ’ FLASH ( 186 ) with protons is performed where exploitation of the BP may be considered redundant to maintain a high, effective mean dose rate whilst also resulting in the FLASH effect ( 184 ). Several transmission studies have been reported ( 177 , 178 , 187 ) as this method is achievable with current technologies. This bypasses the need for additional beam modification devices, minimizing range uncertainties and delivery requirements.…”
Section: Emerging Applicationsmentioning
confidence: 99%
“…In proton FLASH-RT, transmission proton beams have been the most favorable choice of delivery owing to the sufficiently high beam current achievable with existing clinical systems. Recent efforts have reported combining transmission proton PBS with FLASH-RT, to translate the technology from bench to preclinic experiments, in aspects including proton systems (11)(12)(13)(14)(15), treatment planning (18)(19)(20)(21)(22)(23), and biological investigations (24,25). Proton PBS FLASH treatment planning plays a crucial role just as conventional treatment planning, but it faces new and unique challenges as the dose rate considerations must be included when evaluating the plan quality.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several treatment planning studies have applied proton PBS FLASH beams to the head and neck (H&N) (19,20,34) and lung cancers (18,22,23,35), with theoretical proton delivery parameters. van de Water et al (19) discussed the feasibility of achieving transmission FLASH with existing and theoretical machine settings, especially the beam current, with the dose rate quantified using the dose-averaged dose rate (DADR).…”
Section: Introductionmentioning
confidence: 99%